Структурно-семантична характеристика фразеологізмів з гастрономічним компонентом - Бєлих, Оксана Миколаївна; Bielykh, Oksana M. (Кременецька обласної гуманітарно-педагогічна академія імені Тараса Шевченка, 2016)
Проаналізувавши структурні особливості німецькомовних фразеологізмів із гастрономічним компонентом, ми дійшли висновку, що найчисельнішою групою є дієслівні фразеологізми, які відрізняються різною структурою, що, в свою чергу, пояснюється здатністю дієслів до комбінування з іменниками, прислівниками, прикметниками. Прикметникові фразеологізми з гастрономічним компонентом слабо представлені в німецькій мові, так як такі фразеологічні одиниці досить часто відносять до іменникових або прислівникових через виконувану ними роль означення в реченні. Розподіл фразеологічних одиниць з гастрономічним компонентом за семантично-тематичними групами дозволяє зробити висновок про те, що більшість проаналізованих фразеологізмів в німецькій мові семантично орієнтовані на людину. Фізичний і емоційний стани, особливості характеру, розумова та фізична діяльності, зовнішність – майже всі прояви життя людини знаходять яскраве відображення у фразеології із гастрономічним компонентом у сучасній німецькій мові.

The article deals with the structuralsemantic characteristics of German phraseological units with gastronomic component. Functional-semantic aspect of the analyzed phraseological units is very important because it reveals not only the nature but also the character of the semantic relations of the linguistic units. Analizing the structural peculiarities of the German phraseological units with gastronomic component, we drew a conclusion that the most countable group consists of the verbal phraseological units, which differ in their structure. This peculiarity is explained by the combinability of such phraseological units with nouns, adverbs, prepositions. The adjectival phraseological units with gastronomic component are used seldom in modern German, because such phraseological units are often classified as nominal or adverbial due to their attributive function in the sentence. Using semantic criterion we classified all analyzed phraseological units into nine lexical groups: phraseological units with gastronomic component, which 1) describe features of character; 2) characterize reduced circumstances; 3) emphasize the age, experience, appearance; 4) characterize the activity; 5) express skills; 6) show the way to the achievement of an objective; 7) denote the abundance; 8) show pranks; 9) express emotions. This devision of phraseological units with gastronomic component allows us to state that the majority of the phraseological units are individual−oriented semantically. Physical and emotional states, personal character and appearance, mental and physical activity – almost all manifestations of a human being find their reflection in phraseological units with gastronomic component in modern German
Structural-semantic characteristic of German phraseological units with gastronomic component.
Keywords: фразеологія; фразеологічна одиниця; фразеологічні одиниці з гастрономічним компонентом; функціонально-семантичний аспект; структурно-семантична характеристика; семантично-тематична класифікація фразеологізмів; phraseology; phraseological unit; phraseological units with gastronomic component; functional-semantic aspect; structurally-semantic characteristics; semantic lexical groups